Implementasi Peraturan Daerah Nomor 1 Tahun 2018 Tentang Pencegahan Dan Peningkatan Kualitas Terhadap Perumahan Kumuh Dan Permukiman Kumuh (Studi Pada Pulau Kambing, Kelurahan Sei. Lakam Barat, Kecamatan Karimun, Kabupaten Karimun) - Muhammad Rosmansyah; Asmah Suska (PUBLIKA : Jurnal Ilmu Administrasi Publik, 2020)
This research is motivated by the problem of slum settlements, which are settlements that are not suitable for habitation due to building irregularities, high building density, and the quality of buildings and facilities and infrastructure that do not meet the requirements. Slum Monitoring and Control is a process to ensure that an area with a high population density has been implemented properly or not. The implementation of Regional Regulation number 1 of 2018 concerning the prevention and quality improvement of slum housing and slum settlements organized by the Housing and Settlement Service of Karimun Regency is not good, the socialization carried out by the Service has not been optimal. The purpose of this research is to find out how the implementation of regional regulation number 1 of 2018 concerning the prevention and quality improvement of slum housing and slum settlements in Kambing Island, Sei Village. Lakam Barat, Karimun District, Karimun Regency. The research method used is descriptive qualitative. The data source used is primary data through interviews with two informants at the Housing and Settlement Area Office of Karimun Regency and two informants from the Kambing Island community, while secondary data is in the form of documents available at the Housing and Settlement Services Office. The data collection techniques used were interviews, questionnaires and observations. And data analysis techniques using a rating scale. This study uses Marrile S. Grindle's theory that the success of policy implementation is largely determined by the policy content (content policy) and the policy environment (context policy). Thus as a whole it can be seen that the implementation of PERDA No. 1 of 2018 concerning the Prevention and Quality Improvement of Slum Housing and Slum Settlements on Kambing Island, Karimun Regency received a total score of 250 in the "Less Good" category. The implementation of this regional regulation has not been maximally carried out. The influence in the community has not been fully implemented. The role of the Agency is related to the ineffective supervision and control carried out.